YFICITIOUS TIME INTEGRATION METHOD FOR SOLVING THE TIME FRACTIONAL GAS DYNAMICS EQUATION - Partohaghighi, Mohammad; İnç, Mustafa; Baleanu, Dumitru; Moshokoa, Seithuti Philemon (Vinca Inst Nuclear Sci, 2019)
In this work a poweful approach is presented to solve the time-fractional gas dynamics equation. In fact, we use a fictitious time variable y to convert the dependent variable w(x, t) into a new one with one more dimension. Then by taking a initial guess and implementing the group preserving scheme we solve the problem. Finally four examples are solved to illustrate the power of the offered method.
Keywords: fictitious time integration method; group preserving scheme; time fractional gas dynamics equation; Caputo derivative